PURITANISM VIS-A-VIS TRADITIONALISM: ISLAM IN MODERN INDONESIA (Harmoni, 2018)
Islamic movement in Indonesia that become  stronger during political reformation in the end of 1990s, has been spread to every segment of society. It has created new religious school students who practice religious dogma. Out of the reality, it gives positive effect  toward societyΓÇÖs faith. This movement has made new Islam  face  which  differs from the old ones. The strong effect  of various inmternational organisations in this country which bring Islamism, has created new puritan and intolerant to various differences in the society. The Wahhabism that is carried by various salafi in this movement  trigger various conflicts among Indonesian moslems. It is because this movement  has  made the pristine Islam and make many reactions  the tradisionalists who accommodative and as majority Indonesia moslems. The new movements has in  fact, invited and strengthened traditionalism. In other words, the born of modern Islamism movement has caused developing  Islam with puritan fundamental  characteristic  face to face with traditionalism as Indonesian Islam mainstream.
Keywords: Gerakan Islamisme di Indonesia; Islamic movement in Indonesia; Wahhabisme; Salafi; the pristine Islam; islam tradisionalis